The running of legal units and coping with legal issues for the effective administration of educational institutions (1998)
The plea for University education was not given serious consideration until the middle of the 1940s, This was the University College of Ibadan, now known as the' University of Ibadan, It was after this , that other higher educational institutions followed. Educational institutions consist of officers, members of staff, both teaching and non teaching and students. In recent times, these institutions have been witnessing an increasing number of litigations on issues that affect the University in relation to its staff, students or the outside community. There is a general awareness by people and even these institutions about their rights and privileges and this has brought about a greater awareness to many higher institutions that if they are not to be dragged at random into fruitless and senseless litigation, there is the need for an establishment within the institution of a legal unit, headed by a senior and experienced lawyer who can advice the principal officers from time to time on the proper and steps to be followed on issues that may have legal implications. This paper examines the importance of legal Units in the educational institutions, the function of such units and consequence of the non existence in an Educational Institutions.